(untitled) (Scientific journal of the Fergana State University, 2023)
The article is devoted to the problem of translation of neologisms in the field fashion and design, which have not yet been described in English-Uzbek dictionaries. It also shows the alternative ways of translation and problems and solutions that translators face with.